PERFORMA PERTUMBUHAN POSTLARVA UDANG VANAME (Litopenaeus vannamei) YANG DIBERI PAKAN Artemia FROZEN DAN Artemia DEKAPSULASI - Riyanti riyanti; Supono supono; Limin Santoso (Universitas Sriwijaya, 2020)
This study was aimed to examine the level of utilization of artemia frozen and decapsulated artemia feed for growth and survival of vaname shrimp postlarva. The experimental design used a completely randomized design (CRD) with three treatments and three replications. The treatments tested were (A) Frozen Artemia, (B) Decapsulated Artemia, (C) Frozen Artemia + Decapsulated Artemia. Research carried out using 6300 PL2 vaname shrimp. Observed parameters include length growth rate and relative weight, feed utilization efficiency,protein efficiency ratio, survival rate and water quality. Feeding frozen artemia provides the best results with a growth in relative weight 128.06 g, feed utilization efficiency of 0.04%, protein efficiency ratio 48.21%, survival rate with a percentage of 56%, and for the relative length growth rate of artemia frozen + artemia decapsulation has the best results of 17.0%. Keywords : Artemia, tilapia, feed, growth